2012
DOI: 10.1371/journal.pone.0034937
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortex Lesions Impair Object-Spatial Integration

Abstract: How and where object and spatial information are perceptually integrated in the brain is a central question in visual cognition. Single-unit physiology, scalp EEG, and fMRI research suggests that the prefrontal cortex (PFC) is a critical locus for object-spatial integration. To test the causal participation of the PFC in an object-spatial integration network, we studied ten patients with unilateral PFC damage performing a lateralized object-spatial integration task. Consistent with single-unit and neuroimaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Subjects were instructed to keep central fixation because the shapes would be presented rapidly on the left or right side of the screen at encoding [1518], which we confirmed with eyegaze position data. This lateralized visual hemifield design capitalizes on the contralateral organization of the mammalian visual system.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…Subjects were instructed to keep central fixation because the shapes would be presented rapidly on the left or right side of the screen at encoding [1518], which we confirmed with eyegaze position data. This lateralized visual hemifield design capitalizes on the contralateral organization of the mammalian visual system.…”
Section: Resultsmentioning
confidence: 54%
“…Recent functional magnetic resonance imaging (MRI) data indicate that bilateral PFC is recruited for cognitively challenging tasks across the lifespan [19], suggesting that working memory recruits bilateral PFC when both hemispheres are available. Collecting EEG data in a lateralized visual hemifield design is a method to examine whether the unilaterally lesioned brain quickly compensates across hemispheres [15, 16]. Behavioral and EEG data were tested for between-groups effects depending on whether stimuli were presented to the visual hemifield contralateral to the lesioned or intact hemisphere.…”
Section: Resultsmentioning
confidence: 99%
“…Although object identity information is relatively invariant, space information is intrinsically relative and must be specified in a given coordinate. This frame-sensitive nature of space coding is surprisingly overlooked in previous research studying the neural mechanisms in identity and space integration (Cichy, Chen, & Haynes, 2011;Rao, Rainer, & Miller, 1997;Schwarzlose, Swisher, Dang, & Kanwisher, 2008;Voytek, Soltani, Pickard, Kishiyama, & Knight, 2012), with space defined only in the retinotopic coordinate. Retinotopic coordinate, though widespread in the early visual system, is insufficient because of the ubiquitous eye movements and object movements in natural vision.…”
Section: Neural Mechanisms Of Frame-centered Representation and Integmentioning
confidence: 99%
“…Our finding of automatic frame-centered representation reveals the context-sensitive nature of identity and space integration, suggesting the importance in understanding object and space integration in a dynamic environment. On the other hand, studies in object and space integration have revealed the important contribution from the prefrontal cortex (Rao et al, 1997;Voytek et al, 2012), raising the possibility that this prefrontal mechanism might work with motion mechanisms (such as V1 and MT) for maintaining a dynamic frame-centered object representation.…”
Section: Neural Mechanisms Of Frame-centered Representation and Integmentioning
confidence: 99%
“…Although the lesions presented here did not extend to orbital cortex nor to the most lateral parts of prefrontal cortex, additional white matter damage is expected to cause disruption of functional networks in which the MPFC participates. Caution should generally be used in interpreting any functional localization arguments (Voytek & Knight, 2010b), especially in lesion studies where recovery may have occurred (Voytek, Soltani, Pickard, Kishiyama, & Knight, 2012; Voytek et al, 2010). Therefore, the study does not allow for strict localization of functions (Posner et al, 1988).…”
Section: Discussionmentioning
confidence: 99%